1994
DOI: 10.1002/bin.2360090402
|View full text |Cite
|
Sign up to set email alerts
|

Abuse and neglect of adults with mental retardation in different residential settings

Abstract: Eighty-two per cent of all cases of abuse or neglect of an adult with mental retardation substantiated by the Abuse Investigation Division of the Connecticut Office of Protection and Advocacy for Persons with Disabilities over a five-year period occurred in ..the victim's residence. Chi square analyses revealed that there was significantly more abuse in institutions and group homes and significantly less in the individual's own home. Furthermore, analyses revealed that there was significantly more personal neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 16 publications
0
14
0
2
Order By: Relevance
“…As expected, the majority of the victims of sexual abuse are female, with the perpetrators being male [68][69][70][71], although males are also reported to be sexually abused. The high prevalence of sexual abuse has been reported in studies among persons with physical disabilities [41,71], intellectual disability [72,73], visual impairments [71,74], hearing impairments [71,75], psychiatric disabilities [31,63,76] and autism [71,77].…”
Section: Sexual Abusementioning
confidence: 95%
See 1 more Smart Citation
“…As expected, the majority of the victims of sexual abuse are female, with the perpetrators being male [68][69][70][71], although males are also reported to be sexually abused. The high prevalence of sexual abuse has been reported in studies among persons with physical disabilities [41,71], intellectual disability [72,73], visual impairments [71,74], hearing impairments [71,75], psychiatric disabilities [31,63,76] and autism [71,77].…”
Section: Sexual Abusementioning
confidence: 95%
“…Persons with disabilities are vulnerable for sexual abuse both at institutions [71,72,78] and at home [70,71]. Sobsey and Doe [71] found that in 37% of cases, the abuse of persons with disabilities took place in situations and places that 'the victim encountered as a result of being disabled' (p. 249), such as institutions and hospitals, and in specialised transport vehicles.…”
Section: Sexual Abusementioning
confidence: 97%
“…Also persons with intellectual disabilities are involved in violent situations as victims (Marchetti & McCartney, 1990; Sobsey & Doe, 1991; Furey et al. , 1994b; Sigafoos et al.…”
Section: Introductionmentioning
confidence: 99%
“…Physical abuse is the most common type of violence directed towards adult persons with intellectual disabilities in caring situations (Marchetti & McCartney, 1990; Furey et al. , 1994b).…”
Section: Introductionmentioning
confidence: 99%
“…(1984), Elvik, e cols. (1990), Tharinger, Horton e Millea (1990), Conway (1994), Furey, Granfield e Karan (1994), Furey e Niesen (1994), Furey, Niesen e Strauch (1994), Sundram e Stavis (1994) e Abramson e Parker (1995) constataram que o abuso sexual ocorre de diversas formas e em diferentes locais. Pode ser praticado por familiares, empregados das instituições como também pelos próprios deficientes.…”
Section: Psicologia Escolar E Educacional 2004 Volume 8 Número 2 199unclassified